2019
DOI: 10.11591/eei.v8i4.1646
|View full text |Cite
|
Sign up to set email alerts
|

On the use of voice activity detection in speech emotion recognition

Abstract: Emotion recognition through speech has many potential applications, however the challenge comes from achieving a high emotion recognition while using limited resources or interference such as noise. In this paper we have explored the possibility of improving speech emotion recognition by utilizing the voice activity detection (VAD) concept. The emotional voice data from the Berlin Emotion Database (EMO-DB) and a custom-made database LQ Audio Dataset are firstly preprocessed by VAD before feature extraction. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…VAD allows the detection of speech regions in a given audio recording. Many studies [27,5,10] have shown that the application of voice activity detection in speech-analysis systems can produce cleaner data and achieve a higher performance. We implement this using Pyannote.audio, an open-source collection of neural building blocks for speaker diarization [9].…”
Section: Audio Pre-processingmentioning
confidence: 99%
“…VAD allows the detection of speech regions in a given audio recording. Many studies [27,5,10] have shown that the application of voice activity detection in speech-analysis systems can produce cleaner data and achieve a higher performance. We implement this using Pyannote.audio, an open-source collection of neural building blocks for speaker diarization [9].…”
Section: Audio Pre-processingmentioning
confidence: 99%